Predicting Sense of Presence and Sense of Community in Immersive Online Learning Environments - McClannon, Terry W.; Cheney, Amy; Bolt, Les; Terry, Krista (Online Learning, 2019)
This study is based on survey research conducted between 2010 and 2017, involving 1053 graduate students using immersive online learning environments for their coursework. Investigators used course structural factors and student engagement factors to predict students’ perceptions of community and presence in the online immersive space. Utilizing the Sense of Community II index (SCI-2) and the Community of Inquiry survey (COI) median scores as cut scores for predicted outcomes, researchers demonstrated that purely online environments which encouraged student engagement in the online immersive space can enhance sense of presence and sense of community.  In addition, students in graduate programs that used online immersive delivery methods longer developed a stronger sense of community. Both dependent measures proved to have stable subscale structures for this inquiry based on a cursory confirmatory factor analysis